2015
DOI: 10.5455/ajvs.179458
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Effect of Curcumin on Thioacetamide Induced Liver Fibrosis

Abstract: The objective of the present study was to elucidate whether serum ATX activity might be a target for regulation of liver fibrosis and to evaluate the hepatoprotective and antifibrotic effect of curcumin in TAA induced liver fibrosis in rats. Therefore 40 healthy adult albino rats, divided into 4 groups (10 rats in each). Rats in the 2 nd group received curcumin (500 mg/kg b. wt /orally every day), the 3 rd group injected by thioacetamide (TAA) intraperioteneal (250 mg/kg b. wt) three times a week, the 4 th gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Histopathologically, severe alterations of liver structure with fibrogenesis processes were noted. Similar observations were detected in many experimental studies on TAA induced relative influences (Al-Attar, 2011, Al-Attar, 2012, Mustafa et al, 2013, Ali et al, 2014, Abdou et al, 2015, Al-Attar and Shawush, 2015, Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Histopathologically, severe alterations of liver structure with fibrogenesis processes were noted. Similar observations were detected in many experimental studies on TAA induced relative influences (Al-Attar, 2011, Al-Attar, 2012, Mustafa et al, 2013, Ali et al, 2014, Abdou et al, 2015, Al-Attar and Shawush, 2015, Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…The hepatic toxic chemical TAA has been widely used in the study of the underlying mechanisms of hepatic fibrogenesis and the therapeutic effects of potential antifibrosis drugs. Additionally, many experimental investigations showed that TAA induced hepatic fibrosis and cirrhosis in rats and mice (Al-Attar, 2011, Al-Attar, 2012, Ali et al, 2014, Abdou et al, 2015, Al-Attar and Shawush, 2015; Meng et al, 2015, Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that the administration of TAA for three and six weeks induced an elevation in the levels of serum ALT, AST, ALP, GGT and total bilirubin in rats, since necrosis or membrane damage releases these enzymes into circulation, which agrees with the previously reported results ( Kew, 2000 ). Moreover, many investigations showed that these parameters were significantly enhanced in experimental animals exposed to TAA ( Al-Attar, 2011 , Al-Attar, 2012 , Ali et al, 2014 , Kim et al, 2014 , Zargar, 2014 , Abdou et al, 2015 , Al-Attar and Shawush, 2015 , Al-Attar et al, 2016 , Luo et al, 2015 ). Damage of hepatocytes is reflected by an elevation in the levels of hepato specific enzymes (ALT, AST, and ALP), these are cytoplasmic in lection and are released into circulation after cellular damage ( Sallie et al, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…All rats were allowed two weeks as acclimatized period before the beginning of study for adaptation and ensure normal growth and behavior. Rats were randomly separated into 6 groups (10 rats each): control group: received 0.2 ml of distilled water/ 100 g bwt/ day orally (vehicle of TAA and ALA) using a stomach tube three times a week, TAA-treated group: received intraperitoneal (IP) injection of TAA (250 mg/kg bwt dissolved in distilled water) three times a week according to Abdou et al (2015). ALA-treated group: received ALA (100 mg/kg bwt/day) orally using a stomach tube three times a week according to Yousef et al, (2015).…”
Section: Animals and Experimental Designmentioning
confidence: 99%